Individual or team analyst reports? The organization of analyst research activities - CHEN, Xia (Institutional Knowledge at Singapore Management University, 2025)
Given the importance of research resource allocation within brokerage firms, we examine key factors that influence the issuance of individual vs. team analyst reports. Using a comprehensive sample of analyst reports from China for the 2008-2021 period, we find that this decision is influenced by (1) the brokerage firm's client interests, whereby firms held by the brokerage firm's mutual fund clients and firms that are the brokerage firm's underwriting clients receive more team than individual reports from the brokerage firm, and (2) the nature of corporate events, whereby routine events receive more team reports and nonroutine events receive more individual reports. Additional analyses suggest that analysts' personal traits and analyst team characteristics also affect the decision. Our findings further the understanding of the factors that affect the organization and resource allocation of sell-side equity research.